Often Posed Questions (and Answers) Regarding Medicare, Contracting, and Non-Hearing Aid Services - Abel, Debra (Seminars in Hearing, 2019)
Medicare Part B provider participation is often met with grumbling and disdain by most health care providers, including audiologists. Other pain points for audiologists likely include insurance contracts, third-party administrators, and the unknown of the future. The dynamic landscape that will include technology and delivery systems was, until recently, mere thoughts on paper and in conference rooms. With the moderate amount of misunderstanding about Medicare and contracting rules among the members of the profession, it is this article's intent to dispel these Medicare myths as they pertain to hearing and balance services provided by Medicare Part B–enrolled audiologists, to offer considerations in a practice's decision whether to accept commercial insurance and third-party payer contracts, and to offer the tools to position a practice to provide non-hearing aid–related services based on today's current information.
Keywords: Medicare requirements; Medicare advantage plans; third-party administrators; vestibular and tinnitus services